2021
DOI: 10.4103/ijsp.ijsp_220_21
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Addiction among Children and Adolescents – A Review of Qualitative Studies

Abstract: Background: With increasing accessibility to the virtual world, behavioral addiction is an emerging global concern among children and adolescents. Understanding attitudes and perceptions regarding behavioral addictions is critical to formulate appropriately tailored and meaningful interventions. This review aims to widen the scope of understanding behavioral addictions, by synthesizing findings from qualitative studies on perspectives, experiences, and key processes across the spectrum of behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Keeping in mind these aspects, the main aim of this study was to clarify the relationship between some dimensions that characterized adult attachment style and the onset of behaviors that may be included in an adaptive–maladaptive continuum affecting the quality of life and well-being. Particularly, this relationship was detected in a sample including late adolescents and emerging adults due to their reported high involvement in at-risk behaviors as well as in the onset of BA [ 6 , 41 ]. We decided to focus on two behaviors that have been indicated as possible “new addictions” characterized by different degrees of social interaction and included in a range from leisure activity—defining a positive psychological and social frame—to problematic expression—with similarities with addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping in mind these aspects, the main aim of this study was to clarify the relationship between some dimensions that characterized adult attachment style and the onset of behaviors that may be included in an adaptive–maladaptive continuum affecting the quality of life and well-being. Particularly, this relationship was detected in a sample including late adolescents and emerging adults due to their reported high involvement in at-risk behaviors as well as in the onset of BA [ 6 , 41 ]. We decided to focus on two behaviors that have been indicated as possible “new addictions” characterized by different degrees of social interaction and included in a range from leisure activity—defining a positive psychological and social frame—to problematic expression—with similarities with addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The first result found in this study confirms a certain grade of complexity of the BA. Previously, Manohar et al [ 41 ], in an interesting synthesis of qualitative studies on BA, reported that there are multiple dimensions to consider when referring to problematic behaviors, especially in adolescence (age range: 10–20) when the onset is more likely. The authors highlighted the importance of referring to a “spectrum of BA”, defined as a continuum of severity (adaptive–maladaptive), and the impact on the quality of life of the behaviors that may evolve in addiction.…”
Section: Discussionmentioning
confidence: 99%